Abundance patterns (1984-1987 / 1994-1998) of polychaete worms (Annelida) from an estuarine tidal flat, Pacific, Costa Rica - Vargas Zamora, José A. (2015)
The objectives of this report are to provide an updated list of the annelid polychaete worm species found at a tropical estuarine intertidal flat, describe long term oscillations of 11 of the species, and the impact of red tides as evidenced by PCA. From 1984 to 1987 (49 dates) 14 sediment cores (17.7 cm2 – 15 cm deep) were collected per date at low tide from a 400 m2 muddy-sand plot in the Gulf of Nicoya estuary (10o N-85o W), Pacific, Costa Rica. All cores were fixed in Rose Bengal stained formalin and sieved thru a 500 micron mesh screen. A total of 43 species of polychaetes were found and distributed among 25 families and 6600 individuals, of which 80% were represented by: Mediomastus californiensis (32.4%), Caraziella calafia (20.3%), Paraprionospio alata (9.2%), Scolotema tetraura (5.9%), Gymnonereis crosslandi (4.9%), Spiophanex duplex (3.8%), and Glycinde armigera (3.5%). M. californiensis was numerically dominant during most of the sampling dates. The Spionidae (6), Phyllodocidae (4), and Nereididae (3) were the more speciose polychaete families. Populations of all species were patchy in space and time. The abundance patterns of 11 species are illustrated for the 1984-1987 data set. These patterns may reflect declining populations at the beginning of 1984 perhaps influenced by the strong 1982-1983 ENSO event. During 1985 red tides may have influenced the abundances of polychaetes as indicated by the results of a PCA. This is the first time that population patterns of nine species of intertidal polychaetes over a three year period, and the impact of red tides on these worms are reported for this region of the eastern Pacific. General Additive Models (GAM) were applied to the abundances of M. californiensis and P. alata found during 1984-1987 and to additional data from 1994 to 1996 (28 dates) The GAM approach confirmed ealier observations of seasonal oscillations of these species during 1984- 1987, but these trends were not found during 1994-1998. Previously unnoticed underlying patterns of unknown origin were also detected by the application of GAM. The theoretical framework needed for the interpretation of results from tropical benthic surveys could improve significantly from more long term monitoring. Long term abundance data is essential to evaluate the impacts of anthropogenic activities in estuaries.